"Suspended lives": Institutional challenges towards refugees' self-determination” - Santos, P.; Mateus, S. (VIII International Conference of Sociology and Social Work “The Challenges of Democracy: Making Society in Times of Individualization”, 2019)
Four years have passed since asylum applications in Europe reached their peak. From that moment onwards, there’s been a consistent remission of the influx. In 2018 requests dropped to nearly half of those in 2015. While numbers might contribute to political rhetorics claiming that the so-called European refugee crisis has come to an end, the critical scenarios are far from being over. On one hand, it has revealed the frailty of the EU’s humanitarian and democratic values. Specially in those countries where populist nationalism is on the rise, promoting xenophobic attitudes. On the other, asylum seekers and refugees are still facing big challenges related to integration and participation in social life. The inefficiency of organizations in providing support, has showed the limitations of highly bureaucratized systems in responding to the demands of increasingly complex and pluralistic societies. In other words, the forces of social acceleration (Rosa, 2010) and rapid social change are overrunning institutional responsiveness, while creating conditions for alienation. Drawing from the results of 14 semi-structured interviews to asylum seekers and refugees, and one focus group with 12 stakeholders, this paper will focus on experiences of integration and participation in Portuguese society, highlighting the (missing) nexus, between agency and structural factors, that determine the subjects’ autonomy. This study is part of a greater body of research within the framework of the PandPAS project, backed by the EU’s AMIF, which objective is to develop improved processes of welcoming and first integration.